Dinâmica, competição e distribuição espacial em um fragmento de floresta ombrófila mista - Lisboa, Gerson dos Santos (2014)
The present research analyses the dynamics, competition and spatial distribution of individuals in a fragment of mixed ombrophylous forest, in a monitoring period between 2002 and 2011. The study area is located in National Forest of Irati - PR, between the cities of Irati, Fernandes Pinheiro, Teixeira Soares and Imbituva, mid-south region of the Paraná state. The sample was divided into 25 sample units (conglomerates) of 100 m X 100 m (1 ha), subdivided into four subunits of 50 m x 50 m (0,25 ha), and these subdivided in five control ranges of 10 m x 50 m, totaling 20 ranges of 0,05 ha, where each individual tree was numbered, identified, mapped and measured the dbh ≥ 10 cm. The average annual increase for the species Araucaria angustifolia (Bertol.) Kuntze, Cedrela fissilis Vell. and Ocotea porosa (Nees & Mart.) Barroso was 0.18 cm yr-1, 0.22 cm yr-1 and 0.24 cm yr-1, respectively. The average annual increment by diameter class, presented in class 9 (middle class 95) 0.49 cm yr-1. During the study period, there was a decrease of 3.16% in the number of individuals. Four probability density functions (Meyer Type I, II, Weibull 2 and 3 parameters) were used to adjust the diameter distribution for the species Araucaria angustifolia, Cedrela fissilis, Ocotea porosa. In the clustering analysis was used hierarchical agglomerative method and the similarity between the parcels by squared Euclidian distance method and after the groups obtained, it was performed a discriminant analysis aiming to obtain discriminant functions to classify them into graphs of ordination and to test the significance of the groups. The adhesion test of Kolmogorov-Smirnov stated that the Probability Density Function Weibull 3p was the one that followed the specified distribution (at the probability level of 0,95 "α = 0,05). The diversity index of Shannon-Wiener ranged from 3.23 to 3.27 nats ind.-1, indicating that during the period there were changes in diversity. In grouping analysis indicated the formation of floristic groups, and the thrird group showed the more distant linking values between the groups. The spatial distribution of individuals (Araucaria angustifolia, Cedrela fissilis and Ocotea porosa) followed the standard aggregate. To detect level at which occurs separation of the spatial pattern, the Ripley's K function was used, which has the characteristic of detect the maximum point which occurs aggregate pattern, then present the complete spatial randomness standard. In estimating crown diameter used the mathematical model of the second degree, resulting in the equation: with R ² = 0.6582, CV% = 5.02 and F = 163.68. The salience index ranged from 21 to 37 times, in other words, crown diameter greater than the dbh. Individuals located very close to the object tree exert greater influence than more distant object trees, but this sampling method all individuals contribute to the punctual density with its size and distance. For a crown radius 8 m, the results indicate that the density affects growth (annual average increase), indicating that the growth at high density is lower, and in general large individuals are in the upper canopy forest and benefit the condition of direct light in the crown. Multivariate analysis was adequate to distinguish groups based on levels of diversity, an interesting tool for studying management and ecology. The three species (Araucaria angustifolia, Ocotea porosa and Cedrela) showed variations in spatial distribution depending on the spatial scale, the number of individuals and size classes considered. For Araucaria angustifoliaand Ocotea porosa the pattern ranged from random to aggregated, suggesting that these species show high variation in their abundances on scales analysed. For Cedrela fissilis the spatial pattern was random, tends to regulate small spatial scale. The index of competition was significant in the analysis increment in diameter to the crown radius of 8 m, ie, in places with the lowest index of competition, showed greater diameter increment. For radius crown of 4 an 6 m, the index was not significant, ie, increased competition between individuals, not responded positively to the increment.